A flow cytometric granularity assay for the quantification of infectious virus. Issue 47 (8th November 2019) - Logan, Megan; Manalil, Julia; Notte, Christina; Kearse, Craig; George, Steve; Zeiser, Arno; Farrell, Patrick; Aucoin, Marc G.
Abstract: A flow cytometry-based assay was developed to assess the infective titer of two recombinant viruses: a recombinant herpes simplex type 2 (rHSV-2) and a recombinant canary pox (rALVAC.gfp). This method uses granularity of infected Vero and QT-35 cells, respectively, and correlates this to the infectious titer of virus samples. The percent of the cell populations with a high level of granularity could accurately be correlated to viral titers obtained through a traditional plaque assay, with R 2 values greater than 0.8 using a semi-logarithmic scale. This approach offers a rapid, high-throughput method for infectious virus titration with similar accuracy to a traditional plaque assay.